2010
DOI: 10.6063/motricidade.6(1).157
|View full text |Cite
|
Sign up to set email alerts
|

Validação preliminar de um questionário para avaliar as necessidades psicológicas básicas em Educação Física

Abstract: A teoria da autodeterminação é uma a abordagem psicológica sobre a motivação, que se preocupa com as causas e as consequências da forma como o ser humano regula o seu comportamento. Segundo vários autores, este modelo teórico pode fornecer informações importantes sobre o processo motivacional dos alunos para as aulas de Educação Física, no entanto, em Portugal não existe ainda nenhum instrumento de avaliação das necessidades psicológicas básicas neste contexto. Desta forma, o objectivo principal deste estudo é… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 36 publications
(51 reference statements)
1
20
0
7
Order By: Relevance
“…This supports using the measurement model in different cultures, for which the scientific evidence was posteriorly confirmed in a transcultural study regarding the invariances of the measurement model of the BPNES between Greece, Turkey, Spain and Portugal (Vlachopoulos et al, 2013). Further, the Portuguese version of the BPNESp was also adapted and validated preliminary for the physical education context (Pires, Cid, Borrego, Alves, & Silva, 2010), whose model was confirmed in a transcultural study between Portugal and Brazil, where it supported the adequacy of the measurement model for these two countries, as well as their invariance (Cid et al, 2016). In addition to this evidence, some multi-sample studies over the past few years have shown that the basic psychological needs are equivalent across gender, i.e.…”
Section: Introductionmentioning
confidence: 70%
“…This supports using the measurement model in different cultures, for which the scientific evidence was posteriorly confirmed in a transcultural study regarding the invariances of the measurement model of the BPNES between Greece, Turkey, Spain and Portugal (Vlachopoulos et al, 2013). Further, the Portuguese version of the BPNESp was also adapted and validated preliminary for the physical education context (Pires, Cid, Borrego, Alves, & Silva, 2010), whose model was confirmed in a transcultural study between Portugal and Brazil, where it supported the adequacy of the measurement model for these two countries, as well as their invariance (Cid et al, 2016). In addition to this evidence, some multi-sample studies over the past few years have shown that the basic psychological needs are equivalent across gender, i.e.…”
Section: Introductionmentioning
confidence: 70%
“…A questionnaire was applied to assess basic psychological needs in physical education (NPBEF), adapted for Portuguese by Pires, Luís, Borrego, Alves, and Silva (2010) from the Basic Psychological Needs in Exercise Scale (BPNESp) (Vlachopoulos & Michailidou, 2006) and validated for the Brazilian population by Lettnin (2013). The questionnaire consists of 12 items encompassing three dimensions: autonomy (e.g.…”
Section: Measurementsmentioning
confidence: 99%
“…Through the analysis of Table 3 we can see that the answers to items OE_1, OE_4, OE_7, OE_8, OE_9 and OE_10 do not have a normal distribution, since the standard value (Z value) (PIRES et al, 2010).…”
Section: Discussionmentioning
confidence: 99%